Recent advances in processing of titanium alloys and titanium aluminides for space applications: A review - Anil Kumar, V.; Gupta, R. K.; Prasad, M. J. N. V.; Narayana Murty, S. V. S. (Journal of materials research, 2021)
The results of untiring efforts by the research community over the past few decades have led to the successful development and processing of a number of advanced titanium alloys with widely varying properties that can cater to niche applications. Advanced titanium alloys on one hand challenge structural steels with their higher specific strength coupled with their low temperature capability down to 4 K and pose serious threat on the other hand to superalloys for long-term applications up to 773 K. An improved understanding of the processing-microstructure-mechanical property correlation led to the realization of large scale as well as performance critical titanium alloy products in space arena. Recent advances in additive manufacturing, wherein the desired components are directly 3D printed from pre-alloyed powders/wires have given a definite advantage for cost-prohibitive titanium alloys. This review article discusses challenges in the processing, mechanical properties and microstructure evolution of various grades of titanium alloys. It also provides useful information for researchers working on titanium alloys with a glimpse in to the recent advances in Ti alloys and transformation of scientific knowledge to technological advancements in products for space applications. Graphic Abstract